Split-thickness skin graft donor-site dressings: is it possible to establish the ideal dressing based on a literature review? - Rafael Vilela Eiras Ribeiro; Osíris José Dutra Martuscelli (Revista Brasileira de Cirurgia Plástica)
This study aimed to assess the possibility of establishing the most suitable split-thickness skin graft donor site dressings on the basis of scientific evidence gathered through a literature review. The most relevant studies originally published in any language in the last 7 years and indexed in the US National Library of Medicine (PubMed), Cochrane Central Register of Controlled Trials (CENTRAL), and Latin American and Caribbean Literature Health Sciences (LILACS) databases were evaluated. A literature survey was performed using keywords related to the theme and inclusion and exclusion criteria. The final sample comprised 25 publications, one domestic and 24 international. The results showed a gap in the literature with respect to studies that evaluated different split-thickness skin graft donor site dressings. The literature review revealed the impossibility of establishing the most effective split-thickness skin graft donor site dressing due to the lack of scientific evidence, thus preventing the formulation of a definite conclusion on this topic.